On the authentication and re‐authentication protocols in LTE‐WLAN interworking architecture. Issue 4 (3rd March 2016) - Alezabi, Kamal Ali; Hashim, Fazirulhisyam; Hashim, Shaiful J.; Ali, Borhanuddin M.; Jamalipour, Abbas
Abstract: For mobile users, interworking environment composed of Long Term Evolution (LTE) and wireless local area network (WLAN) has become a practical consideration. As a prevalent technology, LTE has desirable features that support high data rate, mobile capabilities, good quality of service and wide coverage area. On the other hand, WLAN network provides higher bit rate but weaker mobility support. Additional features such as cost effectiveness on covering signal‐deadzones of LTE networks and its plentiful bandwidth for better good quality of service make the WLAN a complementary solution for LTE networks. Accordingly, the combination of both technologies would provide better system with higher privilege to both users and service providers. Recent development in LTE‐WLAN interworking has led to a need of authentication protocols that can provide secure and seamless handover process among such networks. Several studies have modified the existing authentication protocols, but they are limited to 3G‐WLAN interworking architecture. Besides, most of the existing authentication schemes are complex and vulnerable to network attacks (e.g. user identity disclosure). Extensible Authentication Protocol with improved authentication and key agreement protocol is introduced in this paper to present the new inter‐re‐authentication and intra‐re‐authentication protocols specified for the LTE‐WLAN interworking architecture. The proposed protocols are verified using Automated Validation of Internet Security Protocols and Applications, and the performances are evaluated in terms of energy consumption, authentication delay and signalling cost. The results indicate that the proposed protocols are more secure and efficient compared with standard protocols. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Extensible authentication protocol with improved authentication and key agreement protocol is introduced in this paper to present the new inter‐re‐authentication and intra‐re‐authentication protocols specified for the LTE‐WLAN interworking architecture. The proposed protocols with modified EAP‐AKA ′ are aimed to reduce the authentication delay, energy consumption, communication cost and at the same time ensuring the security aspects in authentication process. A new mechanism to renew the re‐authentication identity and new key hierarchy is proposed.